Uncovering motives and rivalry of China-Australia amid the COVID-19 pandemic in the Pacific region - Aryo Bimo Prasetyo; Achmad Ismail; Muhammad Fachrie (Masyarakat, Kebudayaan dan Politik, 2021)
The rivalry between China and Australia in the Pacific region shows high tension. This rivalry has increasingly intense in the form of providing assistance to deal with the COVID-19 pandemic, where both countries have various motives of interest by providing the assistance. This article aims to describe the economic and political motives of China and Australia in order to provide assistance in handling COVID-19 to countries in the Pacific region. This article used a descriptive method by collecting several sources from books, journals, official documents, and scientific articles on the internet. It finds that China and Australia have economic and political-security motives from the assistance provided to countries in the Pacific region. The large natural resources in the Pacific region and its transformation into a world maritime trade route become the economic motives. The political motives for China are the principle of “One China” and a “Good Image/Perception” for China, while the political motive for Australia is strengthening Australia’s solidarity in the Pacific region. This article concludes that China’s presence in the Pacific region, which includes assistance in combatting COVID-19 and other concerns, puts China a threat to Australia, making the rivalry between the two countries is no longer inevitable.